ANALYSIS OF STUDENTS ERRORS IN WRITING RECOUNT TEXT (A Case Study in the Tenth Grade Students of SMA Free Methodist Medan ) - Silaban, Betty; Tarigan, Natalia Widya Pasca (English Language Teaching Prima Journal (ELT), 2023)
ABSTRACTThe main objective of this descriptive study was to investigate and categorize the mistakes made by 10th-grade students at SMA Free Methodist Medan when they wrote recount texts. Researchers assessed with a written test, which found 168 errors. The study showed that the five most common types of errors occurred, with misspellings being the most common accounting for 58 errors (35%), pronoun usage with 17 errors (10%), simple past tense with 46 errors (27%), punctuation with 23 errors (14%), and preposition usage with 24 errors (14%). Among them, spelling errors were found to be the most dominant, accounting for 35% of the total errors. The researchers also analyzed the causes of these errors and identified three main factors: first language interference with 51 errors (36%), carelessness with 71 errors (50%), and translation with 20 errors (14%). Carelessness was found to be the primary cause, contributingto50% of the errors.